BIOPROSPECTING OF MARINE SPONGE (CALLYSPONGIA DIFFUSA) FOR ANTIBACTERIAL COMPOUND. - D, Bindu; T, Vinoth Kumar; D, Geetharamani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Marine sponges are a rich source of new antimicrobial drugs. The present study was aimed to evaluate the antibacterial activity of the marine sponge (Callyspongia diffusa) against human pathogenic bacteria and to analyze the presence of bioactive compounds in the sponge. Methods: Antibacterial activity of the marine sponge C. diffuser was examined using petroleum ether, chloroform, n-butanol, methanol, ethanol, and water as solvents and tested against human pathogenic bacteria such as Esherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus by agar well diffusion method. Zoochemical analysis was performed to screen for the presence of secondary metabolites. Bioactive compounds were purified by thin layer chromatography (TLC) and were identified by gas chromatography-mass spectrometry (GC-MS) analysis. Results: The results obtained show that the sponge extracts had significant antibacterial activity against the tested strains. The methanol extract was found to be the most effective and exhibited the highest potency against all pathogens tested. Zoochemical analysis revealed the presence of alkaloids, terpenoids, and sterols. In TLC, spots corresponding to a Rf value of 0.67 were found to possess antibacterial activity against the test bacteria. GC-MS chromatogram showed seven major peaks at retention time of 12.69, 13.81, 24.21, 24.65, 28.01, 28.93, 30.87 minutes. The mass of the compounds and fragments were matched with the National Institute of Standard and Technology (NIST) database for identification of probable compounds present in the sample. GC-MS analysis revealed the presence of bioactive compounds in the sponge. Conclusion: This study confirms the marine natural species provides an excellent source of bioactive metabolites that can exploit to develop novel and potential therapeutic agents.